English Language-Based Higher Education Programmes in East Asia as a Public Diplomacy Instrument: A Pilot Case Study of China and South Korea (Халықаралық қатынастар және халықаралық құқық сериясы, 2023)
Modern public diplomacy scholarship recognises the role of exchange programmes as a public diplomacy tool for both sending and receiving countries. However, the vast majority of scholarship focuses on the exchange experiences of international students in officially or technically English-speaking countries. The internationalisation of higher education and competition in the international higher education market have led to the proliferation of English language higher education programmes in countries where English is not considered a native language. This paper is an attempt to fill the research gap by examining English-language higher education programmes in South Korea and China from a public diplomacy perspective. By conducting a series of in-depth interviews with students and professors/administrators representing English language-based programmes, the study aims to provide a preliminary understanding of whether such educational programmes function as public diplomacy for South Korea and China. The research found that, in contrast to the case of China, there was limited cooperation between Korean scholars and international scholars based in Korea. Friendships and networks with local students were not strong in either country. Overall, however, students in both South Korea and China were satisfied with their experience in the country, which may, at least in part, contribute to perceptions of the host country. The paper concludes that English language-based programmes are indeed a public diplomacy tool for South Korea and China in the selected cases. Further generalisations require additional investigations.Key words: international higher education, English language-based higher education program, public diplomacy, South Korea, China, education diplomacy, exchange diplomacy, academic cooperation, country image, nation branding